Analysis Effectiveness Performance Appraisal On Improving Performance in Koperasi Asrama Mahasiswa ITB - Asmi, Holil; Pangestu, Aria Bayu (Journal of Business and Management, 2021)
Performance appraisal is an important component in the human resource managementprocess, the performance appraisal program serves to monitor employee performance, motivatemembers and increase organizational morale. In the Koperasi Asrama Mahasiswa ITB, theperformance appraisal of employees in the economic division cannot increase the productivity andperformance of employees. Performance appraisal currently does not have formal procedures and clearcriteria for assessing member performance. So that organizations face problems where manyperformance programs fail, and members are not responsible. Therefore, this study was conducted todetermine the effectiveness, determine the factors that cause ineffective performance appraisals in theeconomic division of the Koperasi Asrama Mahasiswa ITB, and how to improve it. This study uses anarrative method and relates the stories the researcher heard through interviews and studying currentperformance appraisal activities. The results of the effectiveness will show what factors influence thecurrent performance appraisal and will show how the effectiveness of the performance appraisal in theKoperasi Asrama Mahasiswa ITB is. This study recommends the organization in makingimprovements that must be made to improve the system as an increase in the effectiveness of theorganization's assessment.Keywords: Economic division, Effectiveness, Performance Appraisal, Student DormitoryCooperative.